The influence of ITT analysis on the evaluation of success rate in the stress urinary incontinence treatment with IVS tape - Surkont, Grzegorz; Wlaźlak, Edyta; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
There are several options to minimize bias during analysis of the results of treatment. It is not possible to organize double blind studies for operative stress urinary incontinence treatment. Aim of the study: The aim of the study was to evaluate the influence of different methods of analysis on results of stress urinary incontinence treatment with IVS tape. Material and methods: We analyzed 50 patients planned for IVS operation. Before the procedure and half year later we provided urogynecology exams according to protocol. The results were evaluated with the use of ITT and modified ITT analysis. For comparison we used previously used method of analysis. Results: Differences between different methods of analysis according to different methods of urogynecological exams were between 3% to 20%. Conclusions: 1. During planning diagnostic methods for the analysis of stress urinary incontinence treatment we should take into account the possibility of obtaining the results. 2. More invasive method less possibility to provide the exam.